Fragmented cities in Latin America in the context of class struggle: a study from dialectical historical materialism based on the tradition «Por beber una copa de oro» («For drinking a cup of gold») - Ortiz Curinambe, Abigail (2024)
The current mode of production, along with its implications, is undeniably manifested in all aspects of our daily lives, as we find ourselves subjugated by a system that favours those who hold property rights and their interests. This phenomenon also leaves its mark on cities, which are built by elites, repeatedly disengaging from their social responsibility, obeying the logic of capital, while the needs of marginalised communities are generally ignored and forgotten. However, in the midst of this global hegemony, resistance movements emerge that challenge the imposed conditions. Through this article, we seek to promote a dialogue from the perspective of dialectical historical materialism, exploring the importance of architecture and urbanism as a reflection of social configuration, using the case of the village of Tintay (Aymaraes, Apurímac) in the tradition «Por beber una copa de oro» («For drinking a cup of gold») and the case of Latin America as a representative testimony of the struggle of the less privileged population.